Distribution of values of additive functions on short intervals - Taranenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider a family of completely additive functions βq(n) defined on the set of natural numbers. We find an asymptotic expression for the summation function Σ n≤x β q (n study its distribution on short intervals.